(untitled) (Research, Society and Development, 2021)
Objective: to ascertain the level of knowledge of the nursing team regarding the handling and control of cuff pressure in order to prevent complications. Methodology: This is a quantitative, empirical, analytical study. The study was developed in the ICUs of a public hospital of Urgency and Emergency, in the metropolitan area of ​​Belém. Nursing professionals. Results and discussion: 30% of respondents answered the option that there is no ideal cuff pressure, but a minimum pressure that is sufficient to seal the trachea; 21.7% considered the ideal pressure to be less than 10 cmH2O; only 18.3% of professionals gave their opinion between 20 to 30 cmH2O and 15% declared they did not know. When addressing the maximum acceptable pressure to avoid causing injury, 20% of professionals defined the value of 10 cmH2O as the maximum limit; 20% said they did not know, and only 16.7% of professionals cited 30 cmH2O as the maximum limit. Conclusion: it was noticed that the respondents demonstrated insufficient knowledge in relation to the ideal pressures and the maximum acceptable pressure not to cause injury, as well as the repercussions. Becoming essential the implementation of permanent education related to the theme, as a way to train the professional for this procedure, collaborating actively in reducing the rates of recurrent complications and inadequate cuff pressure.